Risk Mitigation on Metalworking Oil & Fluids Business Process by Integrated House Of Risk (HOR) and Fishbone Diagram Approach - Natalia, Christine; Oktavia, Chendrasari Wahyu; Silaban, Sonia Artha Ria; Surbakti, Feliks Prasepta Sejahtera (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2021)
Business processes take an essential role in creating strategic goals for every company. However, It is not easy things in current condition. In the business process, every company has many vulnerable activities to risk. This research was conducted in the company engaged in the manufacturing industry that produces and supplies metalworking oils & fluids. So far, the company has experienced risk events such as late production and late delivery. This research aims to analyse and design the risk mitigation strategies of the company’s supply chain by using House of Risk and Fishbone Diagram approaches. By integrating these two methods, the root of the risk agent can be specifically identified and make it easier to design risk mitigation strategies. The purpose of this research is to analyse and design a risk mitigation strategy using the integrated HOR and Fishbone Diagram approach in the supply chain of a metalworking oils & fluids company. This research indicates twenty risk events, six priority risk agents, sixteen root of risk agents, and six priority mitigation strategies. The six priority mitigation strategies include implementing reward and punishment for better SOP, starting with briefing every day before activities, providing regular training to the employees, hiring great employees, establishing employee performance appraisal effectively, and maintaining machines preventively.